Arab-Islamic Culture in Teaching Arabic: for Religious Purposes - Sa'idah, Ratna (Al-Wasil, 2023)
Language is an essential component of culture. Man expressed culture in language, and he cannot speak in languages ​​in isolation from culture. As for the relationship of culture in teaching Arabic to non-native speakers, understanding Arab culture is an essential part of learning this language. Speakers other than this language will master it well if they get to know the culture of Arab society sufficiently. The researcher noticed in the book “Al-Arabiyya Bayna Yadaik” Volume 1-3 by Abd al-Rahman bin Ibrahim al-Fawzan and his companions, and found Islamic culture in terms of religious purposes in many phrases, examples, text, dialogue and exercises in all lessons.